Comparison of trunk muscle exercises in supine position during short arm centrifugation with 1 g at centre of mass and upright in 1 g - Frett, Timo; Lecheler, Leopold; Speer, Martin; Marcos, David; Pesta, Dominik; Tegtbur, Uwe; Schmitz, Marie-Therese; Jordan, Jens; Green, David Andrew (Frontiers in Physiology, 2022)
Spaceflight is associated with reduced antigravitational muscle activity, which results in trunk muscle atrophy and may contribute to post-flight postural and spinal instability. Exercise in artificial gravity (AG) performed on a short-arm human centrifuge (SAHC) is a promising multi-organ countermeasure, especially to mitigate microgravity-induced postural muscle atrophy. Here, we compared trunk muscular activity (mm. rectus abdominis, ext. obliques and multifidi), cardiovascular response and tolerability of trunk muscle exercises performed during centrifugation with 1g at individual center of mass on a SAHC against standard upright exercising. We recorded heart rate, blood pressure, surface trunk muscle activity, motion sickness and rating of perceived exertion (BORG) of 12 participants (8 male/4 female, 34 ± 7 years, 178.4 ± 8.2 cm, 72.1 ± 9.6 kg). Heart rate was significantly increased (p < 0.001) during exercises without differences in conditions. Systolic blood pressure was higher (p < 0.001) during centrifugation with a delayed rise during exercises in upright condition. Diastolic blood pressure was lower in upright (p = 0.018) compared to counter-clockwise but not to clockwise centrifugation. Target muscle activation were comparable between conditions, although activity of multifidi was lower (clockwise: p = 0.003, counter-clockwise: p < 0.001) and rectus abdominis were higher (clockwise: p = 0.0023, counter-clockwise: < 0.001) during centrifugation in one exercise type. No sessions were terminated, BORG scoring reflected a relevant training intensity and no significant increase in motion sickness was reported during centrifugation. Thus, exercising trunk muscles during centrifugation generates comparable targeted muscular and heart rate response and appears to be well tolerated. Differences in blood pressure were relatively minor and not indicative of haemodynamic challenge. SAHC-based muscle training is a candidate to reduce microgravity-induced inter-vertebral disc pathology and trunk muscle atrophy. However, further optimization is required prior to performance of a training study for individuals with trunk muscle atrophy/dysfunction.